CT restaging of testicular germ cell tumors: The incidence of isolated pelvic metastases. Issue 8 (August 2016) - Sadow, Cheryl A.; Maurer, Amma N.; Prevedello, Luciano M.; Sweeney, Christopher J.; Silverman, Stuart G.
Highlights: Isolated pelvic metastases in testicular germ cell tumor restaging is rare. No specific risk factor was found to predict isolated pelvic recurrence. Inclusion of pelvic CT in testicular cancer surveillance should be individualized. Abstract: Purpose: We determined the incidence of isolated pelvic metastases at restaging computed tomography (CT) in patients with testicular germ cell tumors to consider if imaging the pelvis could be omitted. Methods: After receiving IRB approval for this HIPAA-compliant retrospective study, medical records of 560 men (mean age 32.8) with 583 testicular germ cell tumors who underwent 3683 restaging CT scans of the abdomen and pelvis were reviewed to determine the proportion of patients with metastatic disease in the pelvis alone, as verified by histology or by resolution after therapy. Chi-square statistical analysis tested the association between factors currently thought to predispose patients to pelvic metastases. Patients were also categorized by clinical stage, tumor histology, and initial treatment. Results: Isolated pelvic metastases were detected in nine (1.6%) of 560 men. Neither bulky abdominal disease (p = 0.85) nor extratesticular invasion by the primary tumor (p = 0.37) were statistically significant in predicting which patients were more likely to have isolated pelvic metastases. Among the nine patients with isolated pelvic recurrence, only three (0.7%) of 408 men with no known pelvic disease at initial staging and no tumor marker elevation at restaging had isolated pelvic metastases. Isolated pelvic recurrence was not statistically different when analyzed by initial stage and treatment. Conclusion: The incidence of isolated pelvic metastases in testicular germ cell tumors at restaging CT is low, but no group of patients was found to be without risk. Therefore, given the small, if any, risk of radiation-induced harm, the decision about whether to include routine pelvic CT in surveillance protocols should be individualized.